2021
DOI: 10.18231/j.ijmr.2021.065
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of manual conventional blood cultures versus automated blood culture system in cases of septicemia

Abstract: : Blood cultures are a proven gold standard method for the identification of causative agents of bloodstream infections. Identification of causative organism along with antibiotic susceptibility plays a pivotal role in proposing suitable antibiotic therapy. Automated blood culture systems show improved monitoring of blood cultures by reducing the time and by ensuring more accurate results when compared to the conventional blood culture system. To isolate the organism from given blood samples of a suspected cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…[12] In this present study Staphylococcus aureus remained predominant among gram positive organisms followed by Escherichia coli which remained predominant among gram negative organisms in the automated blood culture method. This study correlated with the study conducted by Saher L. et al [13] and Sultana Q. et al in 2016 [14] where a predominance of gram positive isolates like Staphylococcus aureus was observed. The present study also showed that automated blood culture system is a better method for isolating and identifying microorganisms like Salmonella typhi.…”
Section: Discussionsupporting
confidence: 91%
“…[12] In this present study Staphylococcus aureus remained predominant among gram positive organisms followed by Escherichia coli which remained predominant among gram negative organisms in the automated blood culture method. This study correlated with the study conducted by Saher L. et al [13] and Sultana Q. et al in 2016 [14] where a predominance of gram positive isolates like Staphylococcus aureus was observed. The present study also showed that automated blood culture system is a better method for isolating and identifying microorganisms like Salmonella typhi.…”
Section: Discussionsupporting
confidence: 91%
“…Bac T/ALERT 3D automated method detects earlier and studies recorded time to detection (TTD) by this method was 15.83 hours, but reported more contaminants compared to conventional method [11]. Major causes of false positive instrument signals include samples with leukocytosis, over -filled bottles and temperature fluctuation during incubation.…”
Section: Discussionmentioning
confidence: 93%